Synthesis of Phthalocyanines with a Pentafluorosulfanyl Substituent at Peripheral Positions. Issue 6 (24th July 2015) - Iida, Norihito; Tanaka, Kenta; Tokunaga, Etsuko; Mori, Satoru; Saito, Norimichi; Shibata, Norio
Abstract: The pentafluorosulfanyl (SF5 ) group is more electronegative, lipophilic and sterically bulky relative to the well‐explored trifluoromethyl (CF3 ) group. As such, the SF5 group could offer access to pharmaceuticals, agrochemicals and optoelectronic materials with novel properties. Here, the first synthesis of phthalocyanines (Pcs), a class of compounds used as dyes and with potential as photodynamic therapeutics, with a SF5 group directly attached on their peripheral positions is disclosed. The key for this work is the preparation of a series of SF5 ‐containing phthalonitriles, which was beautifully regio‐controlled by a stepwise cyanation via ortho ‐lithiation/iodination from commercially available pentafluorosulfanyl arenes. The macrocyclization of the SF5 ‐containing phthalonitriles to SF5 ‐substituted Pcs required harsh conditions with the exception of the synthesis of β‐SF5 ‐substituted Pc. The regiospecificity of the newly developed SF5 ‐substituted Pcs observed by UV/Vis spectra and fluorescence quantum yields depend on the peripheral positon of the SF5 group. Abstract : Bigger and better : SF5 is a "super" CF3 group, and its inclusion in pharmaceuticals, agrochemicals and optoelectronic materials, e.g. phthalocyanines (Pcs), should impart novel properties. Here, the synthesis of SF5 ‐Pcs3 from key intermediates, SF5 ‐phthalonitriles, is reported. The route was regio‐controlled by a stepwise cyanation via ortho ‐lithiation/iodination from pentafluorosulfanyl arenes. The regiospecificity of these SF5 ‐Pcs3 observed by UV/Vis spectra and fluorescence quantum yields depend on the peripheral positon of the SF5 group.